Photodynamic therapy combined with palliative resection and secondary healing for periocular basal cell carcinoma with inadequate surgical margins - Xiaoqing Wang; Ting Zhang; Tianhang Li; Yahui Feng; Li Ma; Dongmei Li; Yeqiang Song; Dongmei Shi (Photodiagnosis and Photodynamic Therapy)
Periocular basal cell carcinoma (pBCC) is the most common malignancy in the periocular region, characterized by local aggressiveness, high incidence, and significant recurrence rates. While surgery is the primary treatment option, achieving complete lesion removal can be challenging due to the sensitive anatomy of this area and associated cosmetic considerations. Recent advancements in photodynamic therapy (PDT) have demonstrated promising efficacy and cosmetic outcomes for superficial BCC, offering alternatives to traditional treatments. However, PDT's effectiveness is often limited by the penetration depth of photosensitizers, particularly for deep tumors. To address these challenges, we developed a regimen that combines palliative surgery with immediate PDT for pBCC cases with inadequate or positive surgical margins. This integrated approach aims to overcome the penetration limitations of PDT while enhancing tumor clearance and preserving cosmetic outcomes. We report on three cases where all patients achieved complete clinical remission, with satisfactory cosmetic results and no recurrence observed during follow-up periods ranging from 12 to 23 months. Our findings suggest that palliative surgical resection, in conjunction with PDT, represents an effective treatment strategy for pBCC. This approach is particularly valuable when standard surgical margins cannot be achieved, especially considering the importance of cosmetic healing.